2013
DOI: 10.7603/s40682-013-0003-1
|View full text |Cite|
|
Sign up to set email alerts
|

Plaguicidas en México: usos, riesgos y marco regulatorio

Abstract: ResumenEl presente documento describe la situación actual referente a la reglamentación de la producción, distribución, almacenamiento y uso de los plaguicidas en México. Se muestran datos de morbilidad como consecuencia del uso de estos productos como un referente de sus efectos sobre la salud humana, así como, los sitios en la República Mexicana en donde la incidencia es mayor. Adicionalmente, se presenta una revisión de la regulación nacional e internacional sobre plaguicidas, así como, las distintas depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
13
0
4
Order By: Relevance
“…While no associations with health outcomes were studied, previous research documents harmful effects of these pesticide exposures in pregnant women and children. Neurocognitive effects and occurrence cancer at an early age [10] are not the only consequences of broad use of pesticides with insufficient control. A review of epidemiological studies in 2008 [11] reported that children exposed to pesticides might have difficulties performing tasks that involve short-term memory and impaired mental development.…”
Section: Discussionmentioning
confidence: 99%
“…While no associations with health outcomes were studied, previous research documents harmful effects of these pesticide exposures in pregnant women and children. Neurocognitive effects and occurrence cancer at an early age [10] are not the only consequences of broad use of pesticides with insufficient control. A review of epidemiological studies in 2008 [11] reported that children exposed to pesticides might have difficulties performing tasks that involve short-term memory and impaired mental development.…”
Section: Discussionmentioning
confidence: 99%
“…Kampire et al, 2012 (Uganda) (5) anterior podría justificar, en parte, los valores encontrados en esta unidad de producción (21) . Se establece que el estado de Chiapas se encuentra en los primeros lugares en el consumo de plaguicidas y fertilizantes para la producción agrícola (café y plátano, principalmente) y dadas las características ambientales de temperatura y humedad, es altamente probable la movilización de los contaminantes orgánicos que tienden a volatilizarse y depositarse en otros sitios lejanos a la fuente de origen.…”
Section: Resultados Y Discusiónunclassified
“…Several tactics of cultural, mechanical, chemical control and application of mineral oils, detergents and plant extracts have been tested (Rangel-Estrada, Ramírez-Rojas & Osuna-Canizalez, 2013); however; the use of organosynthetic pesticides is still one of the most common control tactics (Badii & Flores, 2001). In response to this problem and restrictions on the use of pesticides (Ortíz, Ávila-Chávez & Torres, 2013), new proposals have been developed to implement them for the controlled management of this pest. For this reason, several years ago, studies and proposals on biological control with the natural enemies of this insect were developed in Mexico and the world (Vanegas-Rico et al, 2010;Cruz-Rodríguez, González-Machorro, Villegas-González, Rodríguez-Ramírez, & Mejía-Lara, 2016).…”
Section: Introductionmentioning
confidence: 99%